Experimental investigation on the long-term durability of bond between FRP and masonry substrates - Ghiassi, Bahman (2013)
The characterization of long-term behavior of bond between Fiber-Reinforced Polymers (FRPs) and masonry substrates in a service environment is a crucial issue for design purposes, which requires a full body of experimental and theoretical information. Most of the research in this area has been devoted to FRP-concrete specimens, and the available data for FRP-strengthened masonry components are still lacking. This paper presents the experimental investigation on degradation of bond between glass FRP composite sheets and masonry bricks by performing accelerated aging tests. Masonry bricks strengthened with GFRP sheets are prepared following the wet lay-up procedure and exposed to thermal cycling and constant relative humidity. Single-lap shear bond tests are finally performed for investigating the degradation of the bond after exposure to environmental conditions and the results are presented.